A study on negative oxygen ions shunting based on direct current pulsating co-frequency coupled electric fields method. (September 2020) - Ji, Dafeng; Gong, Jianhao
Abstract: This paper aims to explore the feasibility and stability of negative oxygen ions (NOI) shunting based on direct current (DC) pulsating co-frequency coupled electric field method, and the safeness under a high anion concentration. Negative oxygen ions were obtained under corona electric discharge from high negative voltage, a shunting method which was employed to detach the negative ions and neutral gas was executed with an uncoupled and a coupled electric field. In coupled field, the negative ions were exported with the same electric field derived from the ion emission polar as a guiding polar, while neutral gas was exported from another outlet; In uncoupled electric field, the purity of NOI from guiding polar powered separately is employed as a control group. Safeness test was approached with 2 rats under a normal cage system. The purity(separate) ratio of NOI between the guide outlet and the neutral gas outlet is 8.5, while the separate ratio is 163636.4 in the coupled electric field respectively. The purity of NOI is 18 million per cm 3 in coupled electric field and 9.8 million per cm 3 in uncoupled electric field. The purity of NOI is 180 million/cm 3 under a voltage of -26 kV. The purity and separate ratio of NOI could be improved significantly after using the coupled electric field compared to uncoupled electric field.